2015
DOI: 10.18552/joaw.v5i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Developing Student-Writers’ Self-efficacy Beliefs

Abstract: Based on Social Cognitive Theory (Bandura 1986) research in academic writing and self-efficacy has shown that there is a relationship between students' performance and their belief in their writing abilities (Matoti and Shumba 2011, Shah et al. 2011, Prat-Sala and Redford 2012. Using questionnaires, interviews and an assessed written task, this study seeks to contribute to this research by exploring the relationship between writing proficiency and self-efficacy beliefs of undergraduate students taking an Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…Concerning self-efficacy found in the present study, it is line with studies done by Magogwe, Ramoroka, and Mogana-Monyepi (2015) and Hashemnejad, Zoghi and Amini (2014) who reported similar findings. The results of their studies revealed students' ability in writing and their self-efficacy are not connected.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning self-efficacy found in the present study, it is line with studies done by Magogwe, Ramoroka, and Mogana-Monyepi (2015) and Hashemnejad, Zoghi and Amini (2014) who reported similar findings. The results of their studies revealed students' ability in writing and their self-efficacy are not connected.…”
Section: Discussionsupporting
confidence: 93%
“…However, high self-efficacy alone might not guarantee students' writing improvement and their satisfaction toward using the strategies as it involved other factors such as teaching styles and methods, feedback, etc. (Magogwe, Ramoroka & Mogana-Monyepi, 2015). Thus, this implies that boosting students' self-efficacy for writing together with other aspects such as teaching methods, teacher, content, etc.…”
Section: Possible Low Self-efficacy For Writingmentioning
confidence: 99%
“…The role of self-efficacy in students' writing has become focus of attention from many researchers because it has important roles in the classroom learning (Broaddus, 2012;Kirmizi, O., & Kirmizi, 2015;Pajares, F., Johnson, M. J., & Usher, 2007;Salem, M. S., & Al-Dyiar, n.d.;Stewart, G., Seifert, T. A., & Rolheiser, 2015;Usher, 2009)especially in students writing and the result of study provides a starting point for identifying factors might contribute to students' writing performance (Halm, 2018;Magogwe, J. M., Ramoroka, B. T., & Mogana-Monyepi, 2015)and teacher may consider writing self-efficacy as part of their teaching technique (Jalaluddin, Yamat, 2013) Essentially, writing is to communicate between students and their needs in social interactions. Students can apply and express their ideas, emotions, and feelings with others through their writing results.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, students' writing difficulties are not only based on their cognitive skill but also their own efficacy beliefs. Magogwe et al explained that Self-efficacy refers to people's specific judgments and beliefs about their abilities to perform a task such as writing an essay (Magogwe, J. M., Ramoroka, B. T., & Mogana-Monyepi, 2015).…”
Section: Introductionmentioning
confidence: 99%